Variation characteristics of physical properties and pore-throat structure of carbonate rocks under the influence of CO2 - WU Xiao, LIU Runchang (Youqicang pingjia yu kaifa, 2025)
As China advances toward its dual-carbon goals, CO2 sequestration in saline aquifers is a key pathway. Saline aquifers in southwestern China are rich in resources and hold great potential for CO2 sequestration. However, current studies on reservoir changes caused by CO₂ sequestration in saline aquifers are mainly limited to the macroscopic scale, with a lack of characterization of changes in the pore structure of rocks before and after CO₂-water-rock reactions at the microscopic scale. Taking the carbonate rock saline aquifer of the second member of the Jialingjiang Formation in the Moxi area, central Sichuan Basin, as an example, 20 sets of CO2-water-rock interaction experiments were conducted through laboratory simulation of formation pressure (69 MPa) and temperature (97 ℃). Analytical techniques such as X-ray diffraction, nuclear magnetic resonance, scanning electron microscopy, and computed tomography were used to investigate in depth the evolution of physical properties and pore-throat structures of the carbonate rocks under the influence of CO2. The results showed that: as the reaction progressed, the proportions of clay minerals and quartz in the rock gradually increased, the mass fraction of feldspar minerals decreased significantly, the mass fraction of calcite first decreased and then increased, while the mass fraction of dolomite showed a trend of first increasing and then decreasing. The dissolution of minerals altered the pore-throat structure of the carbonate rock, enhancing pore connectivity, enlarging the pore-throat radius, and increasing porosity and permeability, thereby expanding the pore space within the reservoir. Moreover, the higher the volume fraction of CO2, the more significant the changes in the physical properties and pore-throat structures of the carbonate rock. Under the influence of pure CO2, after 50 days of reaction, the porosity and permeability of the carbonate rock increased by 18.64% and 522.03%, respectively. By revealing the significant effects of CO2-water-rock reactions on the porosity, permeability, and mineral composition of carbonate rocks, these findings provide valuable data support for CO2 sequestration in saline aquifers.